PELANGGARAN MAKSIM KUANTITAS DALAM PERCAKAPAN BAHASA LAMPUNG ANAK-ANAK USIA SEKOLAH DASAR - Syah, Nur Irwan; Nur, Darma Devanza; Prayogi, Rahmat (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Effective communication is an important foundation in the teaching and learning process in elementary schools. However, elementary school children often lack the ability to manage their utterances appropriately according to Grice's cooperative principle, particularly the maxim of quantity. This study aims to describe the forms of violations of the maxim of quantity made by elementary school students in everyday conversations, as well as to analyze the underlying causes. The approach used is descriptive qualitative with an intrinsic case study design. The results show that violations of the maxim of quantity occur in three main forms: providing too little information, providing excessive information, and irrelevant repetition. The factors causing this violation include children's cognitive development, the communication style shaped by the social environment, and the context of interaction. These findings emphasize the need for integrating pragmatic learning into the elementary school curriculum to enhance children's communication skills from an early age. Additionally, the results of this research contribute theoretically to the study of child pragmatics, particularly in the context of the Indonesian language, and serve as a basis for developing more contextual speaking learning materials.